The Effect of National Television Programs on Social Vitality (Case Study of Universities in Bushehr Province) - Mohammad Mahdi lavari monfared; Gholamreza Jafarinia; Mohammad Reza Shahbazi (Iranian Journal of Educational Research)
Objective: This scholarly investigation has been conducted with the objective of examining the influence of national television programming on social vitality, specifically within the context of universities located in the Bushehr province. Methods: The methodological approach of this study is characterized as a survey type, and the statistical population encompasses a total of 51,902 students enrolled in universities across Bushehr province, including Islamic Azad Universities, Payam Noor, and Persian Gulf University. From this population, a sample of 384 students was systematically selected through cluster sampling, employing Cochran's formula for accuracy. The instrument utilized for data collection comprised a questionnaire specifically developed by the researcher to assess the impact of national television programs. The reliability coefficient of the test was evaluated utilizing Cronbach's alpha methodology, yielding a reliability score of 0.87 for the emotional dimension, 0.85 for the behavioral dimension, and 0.86 for the cognitive dimension. Overall, the reliability of the national television program assessment was determined to be 0.87. In the context of validity evaluation, it is noteworthy that the questionnaire underwent scrutiny by several esteemed professors in the fields of humanities and sociology, particularly the distinguished supervisors and advisors, who confirmed both content and form validity. Results: For the purpose of analyzing the data collected, the Pearson correlation coefficient and regression analysis were employed, revealing a significant correlation between national television programs and the enhancement of emotional, cognitive, and behavioral dimensions of social vitality among students at Bushehr province universities (p < 0.05). Conclusions: The findings of this research hold practical implications for the strategic planning of leisure activities for both students and their families.